AUTHORITY OF MIXING STERILE AVAILABILITY BY NURSES IN HOSPITAL CASE STUDY IN HOSPITAL OF BADAN PENGUSAHAAN BATAM - Martini Heniastaty Patuwondatu; Ede Surya Darmawan; Yaslis Ilyas (Jambura Journal of Health Sciences and Research, 2021)
In giving injection drugs to patients, the dispensing of sterile preparations is carried out by nurses in rooms with limited facilities and infrastructure. Dispensing of sterile preparations must be carried out by pharmacists in health care facilities. The purpose of this study was to examine the authority of nurses in dispensing sterile preparations in hospitals. This study uses a qualitative descriptive approach with a case study method, the research location is at the Batam Business Administration Hospital. The results of the study there are no rules that state nurses in hospitals are given the authority to dispensing sterile preparations. The dispensing service for sterile preparations at the Batam Management Agency Hospital has not been carried out by pharmacists but is carried out by nurses. This condition will affect the quality of service in the hospital. Recommendation: Implementing the rules for dispensing sterile preparations by pharmacists, hospitals need to make clear the division of tasks between nurses and pharmacists. Keywords: Authority, Nurse, Hospital, Dispensing Sterile Preparations